Sosialisasi Rules of the Game: Isu-Isu Terbaru Aturan Permainan Bola Voli - Sujarwo, Sujarwo (Empowerment : Jurnal Pengabdian Masyarakat, 2021)
Community service, in this case volleyball coaches throughout Indonesia, regarding the latest volleyball game rules is needed by coaches to always update information and try to adapt to the exercises and strategies that will be applied in their team. The purpose of community service is to provide information and increase knowledge to volleyball coaches about the latest rules in volleyball games. Community service using the online method with the Zoom Meeting application. Participants in this community service activity are volleyball coaches throughout Indonesia, totaling 32 people. The service material is delivered by a national referee who already has an official refereeing license. The target of service is to increase the knowledge of the trainers of the activity participants about the latest game rules. The measurement of the increase in knowledge is measured by calculating the difference in the mean of the results of the pretest and also the results of the posttest of community service activities. The results of community service showed an increase in the mean pretest mean: 79.67 and the average posttest result: 87.09, the average increase in the coach's knowledge of the latest volleyball game rules was: 7.42%. The coach's knowledge of the rules of the volleyball game must continue to be improved, because the faster development of volleyball affects the rules of the volleyball game. AbstrakPengabdian pada masyarakat dalam hal ini pelatih bola voli di seluruh Indonesia tentang peraturan permainan bola voli yang terkini sangat dibutuhkan oleh pelatih untuk selalu update informasi dan berusaha menyesuaikan dengan latihan dan strategi yang akan diterapkan dalam tim mereka. Tujuan pengabdian masyarakat adalah untuk memberikan informasi dan meningkatkan pengetahuan kepada pelatih bola voli tentang aturan terbaru dalam permainan bola voli. Pengabdian masyarakat menggunakan metode daring dengan aplikasi Zoom Meeting. Peserta dalam kegiatan pengabdian masyarakat ini adalah pelatih bola voli di seluruh Indonesia, berjumlah 32 orang. Materi pengabdian disampaikan oleh wasit nasional yang sudah memiliki lisensi perwasitan resmi. Target pengabdian terjadi peningkatan pengetahuan pelatih peserta kegiatan tentang aturan permainan yang terbaru. Pengukuran peningkatan pengetahuan diukur dengan perhitungan dan perbedaan mean rerata dari hasil pretest dan juga hasil posttest kegiatan pengabdian masyarakat. Hasil pengabdian masyarakat menunjukkan peningkatan rerata mean pretest: 79.67 dan hasil rerata posttest: 87.09, peningkatan mean rerata pengetahuan pelatih tentang aturan permainan bola voli terbaru sebesar: 7.42%. Pengetahuan pelatih tentang aturan permainan bola voli harus terus ditingkatkan, karena perkembangan bola voli yang semakin cepat mempengaruhi aturan permainan bola voli.